Hubungan Pola Asuh Orang Tua terhadap Perilaku Kesehatan Gigi dan Mulut Anak Down Syndrome - Syafa Layyina Amalia; Nurdiana Dewi; Riky Hamdani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2024)
Background: Parental, Down syndrome is a trisomy chromosomal genetic disorder that leads newborn child having more than one chromosome so that could interfere the normal growth of the body due to an excess of protein level. Children with Down syndrome have different oral health problems compared to the general population. They need assistance to maintain their oral health because of mental and physical deficiencies as well as limitations in optimally cleaning their teeth. Objective: To analyze the relationship between parenting styles and oral health behavior of children with Down syndrome in Banjarmasin Special Needs School, Indonesia. Materials and Method: This is an observational analytic study with cross-sectional approach. Sample was taken using simple random sampling technique and a cross-sectional sample formula obtained for 32 respondents. The instrument used a parenting style questionnaire and a behavioral modification questionnaire for children's oral health. Results: Democratic (87.5%) compared switch order parenting styles. It was found that there were more children with Down syndrome in the category of moderate behavior (59%) than children with good behavior (38%) and poor behavior (3%). The results of the Somers'd test data analysis obtained a significance value of 0.034 (p<0.05) and the correlation value obtained was 0.571, which means that the correlation strength is moderate with a positive correlation direction (unidirectional). Conclusion: The more democratic the parents use as parenting style the better the oral health behavior of children with Down syndrome will be.